2021
DOI: 10.1007/s13337-021-00667-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an avian GA13-like infectious bronchitis virus full-length genome from Costa Rica

Abstract: We describe the first whole-genome sequence of a GA13-like isolate of avian infectious bronchitis virus CK/CR/1160/16 (MN757859), obtained in 2016 in the province of Alajuela, Costa Rica. This virus caused an outbreak with great economic impact to the local poultry industry. The genome sequence is 27 696 bp in length, with the following genome organization 5′-UTR-Pol-S-3a-3b-E-4b-4c-M-5a-5b-N-6b-3′-UTR. The complete genome sequence has the highest sequence identity (94.03%) with DMV/1639/GA9977/2019 (MK878536)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Our results revealed that IBV/Ck/Can/2558004 had 27, 710 nt long, consisting of 13 ORFs organized as 5′UTR-1a-1b-S-3a-3b-3c(E)-M-4b-4c-5a-5b-N-6b-3′UTR, and this agreed with previously characterized IBV isolates in some parts of the world [ 74 , 75 ]. Additionally, our findings showed the presence of a non-coding region consisting of eight nt located between genes N and 6b, which has been previously recognized [ 76 ].…”
Section: Discussionsupporting
confidence: 75%
“…Our results revealed that IBV/Ck/Can/2558004 had 27, 710 nt long, consisting of 13 ORFs organized as 5′UTR-1a-1b-S-3a-3b-3c(E)-M-4b-4c-5a-5b-N-6b-3′UTR, and this agreed with previously characterized IBV isolates in some parts of the world [ 74 , 75 ]. Additionally, our findings showed the presence of a non-coding region consisting of eight nt located between genes N and 6b, which has been previously recognized [ 76 ].…”
Section: Discussionsupporting
confidence: 75%
“…The entire genome sequence has a sequence identity with that of the strain from Georgia, USA, of 94.03%, and the least similar sequence identity with that of the strain from China is 86.03%. The Costa Rican isolate, which shows 96.89% similarity with the S1 subunit of the Georgian strain, was identified as belonging to genotype I and lineage 17 (GI-17) ( Villalobos-Agüero et al., 2021 ).…”
Section: Genotypic Prevalence On Continentsmentioning
confidence: 99%
“…For example, in North America, various indigenous genotypes have been identified, including GI-8, GI-9, GI-17, GI-20, GI-25, GI-27, GIV-1, GVIII-1, with GI-20 reported exclusively in Canada [74]. Interestingly, GI-17 has been isolated recently from outbreaks during 2016-2017 in Costa Rica [122]. Mexico is endemic with GI-31 and GIX [123] (discussed later in this review).…”
Section: Emergence and Dissemination Of Ibv Variants Worldwidementioning
confidence: 99%